(untitled) (Revista NUPEART, 2023)
This paper aims to promote reflections and introduce ques- tions about educational and creative processes within the scope of the Performing Arts. Thefore, we will seek to discuss two pers- pectives: the pedagogy or system, sui generis, of neoplatonic basis undertaken by François Delsarte and the philosophical and thera- peutic vision of Corporal Reading (CL) shared by Nereida Fontes Vilela. The approach used is content analysis, also using the peda- gogical perspective of the crossroads of Antônio Simas and Luiz Rufino. This intersection of thoughts, disparate modes and know- ledge reveals, each in its own way, that bodily signals are access routes to knowledge rooted in our bodies that carry stories and that need to be felt, validated and experienced.